Documentary history of the mongolian folk song “Soyol erdene”. (Mongolian Journal of Arts and Culture, 2023)
The aim of this study is to explore the life and musical contributions of Dorjdagva Jigzav, a renowned singer and composer of Mongolia. It was the Prime Minister of Mongolia, Amar Anand, who first introduced Dorjdagva J. to the famous singer Dugarjav Magsar khurts. Dorjdagva J. was well-known for his work in the development of long and folk songs, choral singing, and contemporary music. He was committed to preserving and promoting Mongolian music, and his compositions played a significant role in elevating Mongolian music to new level. Additionally, Dorjdagva J. was also a researcher, educator, and teacher of long songs. Together with Dugarjav M. and other composers, he published several collections of Mongolian long and folk songs, including “A Collection of Mongolian Long Songs” in 1935 and 1936, and “108 Long Songs” with their musical notes in 1970. Between 1933-1942, he created his greatest works, which included over 30 songs, more than 10 song lyrics, and 5 pieces of long song music and lyrics. This study is intended to protect the copyright of Dorjdagva Jigzav’s songs, song music and lyrics, recognizing the importance of his contributions to Mongolian music.“Соёл эрдэнэ” дууны баримтат түүхХураангуй: Монгол улсад уртын болон ардын дуу, найрал дуу, шинэ цагийн дуу хөгжмийг хөгжүүлэхэд үнэтэй хувь нэмэр оруулсан гавьяатнуудын нэг бол Анандын Амар сайд Алдарт дуучин Магсар хурцын Дугаржав дуучинтай танилцуулсан анхны Алдарт Гавьяат дуучин Жигзавын Дорждагва юм. Ж.Дорждагва нь монголын урт болон ардын дууны хөгжил, түүний хадгалалт хамгаалалт, өвлүүлэн үлдээхэд онцгой анхаарч, авьяас чадвар, ур ухаан, сэтгэл зүрхээ зориулсан билээ. Монголын хөгжмийн урлагийг шинэ шатанд гаргахад дууны судлаач, сурган хүмүүжүүлэгч, багш, хөгжмийн зохиолч байжээ. Ж.Дорждагва 1935, 1936 онд Алдарт дуучин М.Дугаржав нарын уран бүтээлчидтэй хамтран “Монгол урт дуунуудын түүвэр”, “Монгол ардын дуунуудын түүвэр”, 1970 онд 108 уртын дууг ноотлон, “Уртын дуу” номыг хэвлүүлсэн байна. 1933- 1942 онд дууны хөгжмийн бүтээлийнхээ гол бүтээлүүдээ туурвисан ба нийт 30 гаруй дууны хөгжмийг, 10 гаруй дууны шүлгийг, 5 уртын дууны хөгжим, үгийг зохиосон байна. Ийм учраас үг, хөгжмийг зохиосон дууны зохиогчийн эрхийг хамгаалахыг зорилоо.Түлхүүр үг: түүхэн өв са н, тодруулга, оюуны өмч